Handbuch Sozialwissenschaftliche Gedächtnisforschung - Sebald, Gerd; Berek, Mathias; Chmelar, Kristina; Dimbath, Oliver; Haag, Hanna; Heinlein, Michael; Leonhard, Nina; Rauer, Valentin (Springer VS, 2023)
Überblick zum Stand der Gedächtnisforschung Band 2 - M-Z Umfassend und interdisziplin